Engineering nanosystems to overcome barriers to cancer diagnosis and treatment - Alhaj-Suliman, Suhaila O.; Wafa, Emad I.; Salem, Aliasger K. (Advanced drug delivery reviews, 2022)
[Display omitted] •Progress of preclinical and clinical research into engineered nanomedicine is helping to bring new effective diagnostic and therapeutic approaches to cancer patients.•Biomarker-driven engineered nanoparticles offer enhanced cancer-specific and personalized therapy.•Engineered nanoparticles represent an efficient tool to deliver different types of treatments for patients with difficult-to-treat cancers.•Surface-engineered nanoparticles have the potential to overcome the physical and biological barriers that are known to limit the effectiveness of unmodified or unfunctionalized nanoparticles. Over the past two decades, multidisciplinary investigations into the development of nanoparticles for medical applications have continually increased. However, nanoparticles are still subject to biological barriers and biodistribution challenges, which limit their overall clinical potential. This has motivated the implementation of innovational modifications to a range of nanoparticle formulations designed for cancer imaging and/or cancer treatment to overcome specific barriers and shift the accumulation of payloads toward the diseased tissues. In recent years, novel technological and chemical approaches have been employed to modify or functionalize the surface of nanoparticles or manipulate the characteristics of nanoparticles. Combining these approaches with the identification of critical biomarkers provides new strategies for enhancing nanoparticle specificity for both cancer diagnostic and therapeutic applications. This review discusses the most recent advances in the design and engineering of nanoparticles as well as future directions for developing the next generation of nanomedicines.